Effect of a Hexagonal Barbell on the Mechanical Demand of Deadlift Performance - Jason Lake; Freddie Duncan; Matt Jackson; David Naworynsky (MDPI AG, 2017)
This study compared typical mechanical variables of interest obtained directly from barbell motion during deadlift performance with a conventional (CBD) and a hexagonal barbell (HBD). Eleven men, proficient with both deadlift variations, volunteered to participate in the study (age: 20.3 ± 0.6 years; height: 175.5 ± 8.5 m; mass: 88.7 ± 19.0 kg; CBD 1RM: 183 ± 22 kg; HBD 1RM: 194 ± 20 kg). During the first session, CBD and HBD 1RM was assessed; during the second session, they performed 3 sets of 1 CBD repetition with 90% 1RM; and in session three, they repeated this process with the HBD. Barbell displacement was recorded at 1000 Hz and mechanical parameters derived from this. Significantly heavier loads were lifted during HBD (6%, p = 0.003). There were no significant differences between barbell displacement (p = 0.216). However, HBD was performed significantly faster (15%, p = 0.012), HBD load was accelerated for significantly longer (36%, p = 0.004), and significantly larger mean forces underpinned this (6%, p < 0.001), with more work having been performed (7%, p < 0.001) at greater power outputs (28%, p < 0.001). The results of this study showed that heavier HBD loads can be lifted through the same range of motion faster, and that this load is accelerated for significantly longer. The strategies used to achieve these differences could have a significant effect on training outcomes.